Investigation of Influence of Honing Tool Input Factors on the Roughness Parameter - Urinov Nasillo Fayzilloevich; Saidova Mukhabbat Khamroevna; Mukhitdinov Mekhriddin Muminovich (Genius Journals, 2022)
The article presents a comparative analysis of tools and a study of the influence of input factors of a honing tool on surface quality
Keywords: Honing head; hole; tool; technology